2019
DOI: 10.1149/2.0561908jes
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Phase Cathodes for Metal-Supported Solid Oxide Fuel Cells: Processing, Performance, Durability

Abstract: Cathode processing is one of the main challenges in the manufacturing of metal-supported solid oxide fuel cells (MSCs). Cathode sintering in ambient air is not applicable to MSCs, as oxidation of the metal substrate and the metallic Ni of the anode damages the cell. A recently developed ex situ sintering procedure for the LSCF cathode in an argon atmosphere was shown to significantly improve cathode adherence. However, the stability of the sintered cathode layer posed a challenge during storage in ambient air.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…Furthermore, it has potential as electrochemically active membrane material for oxygen transport membranes [ 4 ]. Recently, our group demonstrated that GDC increases electrochemical activity of Ni-based cermet anodes [ 5 , 6 ] as well as mechanical stability of perovskite cathodes in SOFC [ 7 ], making this material a bright future prospect for manifold applications in the chemistry and energy sector. However, processing of GDC as bulk or membrane material is a challenging task, which usually requires either high temperatures or careful atmosphere control as discussed in more detail below.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has potential as electrochemically active membrane material for oxygen transport membranes [ 4 ]. Recently, our group demonstrated that GDC increases electrochemical activity of Ni-based cermet anodes [ 5 , 6 ] as well as mechanical stability of perovskite cathodes in SOFC [ 7 ], making this material a bright future prospect for manifold applications in the chemistry and energy sector. However, processing of GDC as bulk or membrane material is a challenging task, which usually requires either high temperatures or careful atmosphere control as discussed in more detail below.…”
Section: Introductionmentioning
confidence: 99%
“…However, processing of GDC as bulk or membrane material is a challenging task, which usually requires either high temperatures or careful atmosphere control as discussed in more detail below. The complexity of processing GDC becomes even higher, when it is in contact with other functional materials, which is the usual case in electrochemical devices, e.g., in cermet electrodes [ 5 , 6 , 7 ] or dual phase membranes [ 4 ]. In this work, the focus will lie on problems and solutions in processing of pure GDC by Field-Assisted Sintering Technique, also known as Spark Plasma Sintering (FAST/SPS).…”
Section: Introductionmentioning
confidence: 99%
“…The solution to this problem is to design stable cathode nanometer catalytic materials. Compared with the infiltration method, ex situ sintering is another method that has been used to suppress the cathode’s degradation in recent years [ 119 , 120 , 121 , 122 , 123 ]. The sintering of the cathode on the whole cell is typically performed in argon at 950 °C.…”
Section: Degradation Mechanism and Countermeasuresmentioning
confidence: 99%
“…However, La 2 O 3 was found during the sintering when LSC-based cathode was used, which led to the formation of La(OH) 3 and potentially decreased the performance and durability of cells [ 121 ]. LSC/GDC dual-phase cathode was used to suppress the degradation caused by La(OH) 3 because the rigid GDC network can additional mechanical stability for the cathode, according to Udomsilp et al (2019) [ 120 ].…”
Section: Degradation Mechanism and Countermeasuresmentioning
confidence: 99%
“…Thus, it is used as a catalyst, or as a catalyst support for chemical processing [3][4][5] . It also possesses high ionic conductivity between 500 to 600 °C 6,7 , which makes it a strong candidate for electrochemical devices like oxygen sensors 8,9 , oxygen transport membranes 10,11 , cermet electrodes [12][13][14] and electrolytes for solid oxide fuel and electrolysis cells (SOFC/SOECs) 6,7,15,16 .…”
Section: Introductionmentioning
confidence: 99%